A pilot study on efficacy of group educational training on knowledge level, stress, anxiety and depression in parents of children with autistic disorder - Atosa Rabiee; Zahra Shahrivar (Vesnu Publications, 2011)
Background: there is a paucity of data regarding the efficacy of group education for parents of children with autistic disorder. The aim of this study was to investigate the effectiveness of parental group education in increasing their knowledge about the disease and ways to help autistic children and decreasing their depression, anxiety and stress.                                                                                                           Materials and Methods: twelve parents who had a child with autistic disorder and was referred to Ruzbeh Hospital for treatment participated in a group education program consisting of five two-hour sessions. Before initiating and after completing the program the participants were evaluated via following assessment tools: The Speech-Language-Hearing History Profile, Depression-Anxiety-Stress Scale, Participant satisfaction Scale, and a tailored questioner for assessing parents' knowledge level before and after training.                                                                             Result: Study data showed a significant increase in parents' knowledge level (p< 0.001). The quality of this program was mentioned to be appropriate by the participants. There was no improvement in any measures of the   depression, anxiety, and stress.  Conclusion: Group educational training could be effective in increasing knowledge of parents with autistic children about autism. Additional studies with more samples from different age groups are recommended.                                                                                                                     Key words: autism, group training, parent training